Macroencapsulation of Limosilactobacillus reuteri DSPV002C as nutritional supplement for piglets: Storage stability and survival in gastrointestinal conditions = Macroencapsulación de Limosilactobacillus reuteri DSPV002C como suplemento nutricional para cerdos: viabilidad en almacenamiento y en condiciones gastrointestinales simuladas - Zimmermann, Jorge Alberto; Sirini, Noelí Estefanía; Olivero, Carolina Raquel; Renna, María Sol; Signorini Porchiett, Marcelo Lisandro; Zbrun, María Virginia; Frizzo, Laureano Sebastián; Soto, Lorena Paola (Elsevier, 2025)
The aim of this study was to evaluate the protective effect of the encapsulation of Limosilactobacillus reuteri DSPV002C in macrocapsules made from industrial materials during production, storage and under simulated gastrointestinal conditions in vitro and in vivo. The production of macrocapsules involved the evaluation of different wall materials (matrix), namely, gelatin and pregelatinized starch, different inoculums, matrix ratios, and diverse cryoprotectants (whey permeate and maltodextrin). The different macrocapsules were arranged in molds of similar size to pig pelleted food and lyophilized. Then, the viability of the macrocapsules was assessed over time during storage at different temperatures (freezing, refrigeration and room temperature) and atmospheres (vacuum and non-vaccum). The macrocapsules with 10% w/v gelatin + 5% w/v pregelatinized starch, permeated (10%, w/v), with a 9:1 inoculum:matrix ratio (GS7.5P9), stored under freezing conditions and vacuum, exhibited the highest viability of L. reuteri DSPV002C (9.3 log CFU/cap until 210 d). Under simulated gastrointestinal conditions, the encapsulated inoculum showed less viability loss (0.58 ± 0.09 log CFU/ml, 26.53%), compared to the free culture (1.56 ± 0.16 log CFU/ml, 2.85%). Finally, by administering GS7.5P9 to pigs, the tolerance of the bacteria to the gastrointestinal environment was verified, with viable counts equal to or greater than 3.72 log CFU/g of fecal matter throughout the trial. In this study, a high-density carrier probiotic macrocapsule of L. reuteri DSPV002C was obtained, which displayed a long shelf life, a suitable shape to be included in pig feed and an adequate survival of viable cells at the site of action.